Local thermal characterization of metal sample by stimulated infra-red thermography. (20th June 2014) - Mouhoubi, K.; Bodnar, J.L.; Ousseni, S.; Nicolas, J.L.; Caron, D.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, we consider the possibilities of the stimulated infra-red thermography for local metallic sample thermal characterization. At first we introduce the measurement principle, which is based on the local measurement of the thermal diffusivity parameter. Then, using simulations, we demonstrate the feasibility of the method. We then present the experimental device implemented for the study. Finally, we show that this approach allows a good estimation of the thermal diffusivity of a metal sample.